Evaluation of MR imaging with T1 and T2* mapping for the determination of hepatic iron overload - Henninger, Benjamin; Michaely, Henrik J. M. (European radiology, 2012)
Objectives: To evaluate MRI using T1 and T2* mapping sequences in patients with suspected hepatic iron overload (HIO).MethodsTwenty-five consecutive patients with clinically suspected HIO were retrospectively studied. All underwent MRI and liver biopsy. For the quantification of liver T2* values we used a fat-saturated multi-echo gradient echo sequence with 12 echoes (TR = 200 ms, TE = 0.99 ms + n × 1.41 ms, flip angle 20°). T1 values were obtained using a fast T1 mapping sequence based on an inversion recovery snapshot FLASH sequence. Parameter maps were analysed using regions of interest. Results: ROC analysis calculated cut-off points at 10.07 ms and 15.47 ms for T2* in the determination of HIO with accuracy 88 %/88 %, sensitivity 84 %/89.5 % and specificity 100 %/83 %. MRI correctly classified 20 patients (80 %). All patients with HIO only had decreased T1 and T2* relaxation times. There was a significant difference in T1 between patients with HIO only and patients with HIO and steatohepatitis (P = 0.018). Conclusions: MRI-based T2* relaxation diagnoses HIO very accurately, even at low iron concentrations. Important additional information may be obtained by the combination of T1 and T2* mapping. It is a rapid, non-invasive, accurate and reproducible technique for validating the evidence of even low hepatic iron concentrations. Key Points: Hepatic iron overload causes fibrosis, cirrhosis and increases hepatocellular carcinoma risk. MRI detects iron because of the field heterogeneity generated by haemosiderin. T2* relaxation is very accurate in diagnosing hepatic iron overload. Additional information may be obtained by T1 and T2* mapping.
Gesehen am 07.05.2018